Catalytic Conversion of Castor Oil into Biodiesel by Tri-organotin(IV) Catalysts: Chromatographic and Spectroscopic Characterization with Theoretical Support - Nousheen Mustafa; Muhammad Zubair; Noor Uddin; Saqib Ali; Ali Haider; Amin Badshah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Economic concern over fossil fuel reserves, extensive increase in CO2 emission, and change in the world climate due to the combustion of carbon sources have been driving the attention of both commercial and academic researchers towards new sustainable fuel routes to encounter rapidly growing worldwide population demands. In the present study, we have focused on catalytic transesterification towards the environmentally friendly biodiesel synthesis which is low cost, easily implemented and best alternative source of fossil fuels. Herein three triorganotin(IV) carboxylates derivatives namely trimethylstannyl cyclopentanecarboxylate, tributylstannyl cyclopentanecarboxylate and triphenylstannyl cyclopentanecarboxylate were resynthesized according to our reported procedure and theoretically investigated through DFT by applying LANL2DZ as functional with B3LYP basis set (level of theory) to calculate Molecular Electrostatic Potential (MEP) to determine electrophilic center of complexes and Lewis acidity. Owing to the Lewis acid character, the synthesized complexes were then used as catalysts in the transesterification reaction of castor oil. Different reaction parameters were also optimized to obtain maximum biodiesel yield. Synthesized castor oil biodiesel (COB) was characterized and confirmed by employing multitude spectroscopic techniques. The present study evaluated that these complexes can be potential candidates for biodiesel conversion from non-edible and cheap feedstock.